THE ORGANIZING OF COMPETITIVE EVENTS USING MULTI-AGENT TECHNOLOGIES AND THE MODIFIED BORDA METHOD (Computer systems and information technologies, 2023)
The hackathons allow collecting at once on one site: the largest industrial companies of the country, technology vendors from the rapidly changing environment in the markets, young developers (including students), engineers with experience in the IT-sphere or specifically required technologies.The current state of hackathon organizing stages has analyzed to improve the approach to increase the social inclusion of participants. Statistical metrics of vacancies occurrence probability during the period after the hackathon and employee turnover provided by hackathons’ sponsors according to business domains were investigated.The methods of determining the winner in different systems of competitive selection are considered. Particular attention is paid to the peculiarities of the tournament systems used in cybersport championships. The system of selection based on the modified Borda method, consisting of two or a maximum of three rounds and independent of the number of participants, is proposed.In the paper, the Multi-Agent Sell Funnel Monitoring (MASFM) algorithm has described. MASFM algorithm allows searching sponsorship efficiently because it helps detect about 16–23% of new sponsors according to last 2 years statistics. In the software architecture of the online hackathons’ platform, a real scenario of increasing performance 15 times from 6 to 94 requests/sec was applied, which does not require serious refactoring and complex code changes. Besides, the steps mentioned above can reduce the cost of infrastructure like Heroku. The next functionality of the online hackathon platform will be possible thanks to the microservices architecture.As the result, efficient software architecture has implemented and allow to decrease the maximum response time down to 3 seconds and the online hackathon platform’s performance has increased from 71 to 94 requests per second.
Keywords: eSport event; organizing of hackathon; selection of teams; multi-agent system; algorithm for determining winners; grading procedure